High-rate settlement and unconsciousness with shime-waza in young judo athletes from a video analytic study in Judo World Championships. Issue 11 (November 2022) - Sasaki, Eiji; Ikumi, Akira; Sakuyama, Naoki; Malliaropoulos, Nikos; Mikami, Yasuo; Nagahiro, Shinji
Abstract: Objectives: We aimed to investigate the incidence rate of unconsciousness related to shime-waza and the accompanying symptoms by age categories using video analysis of the Judo World Championships. Design: Observational retrospective study. Methods: We included 6918 elite judo athletes and 7426 bouts from the Judo World Championships between 2015 and 2021. Incidence rates of matches settled using shime-waza and unconsciousness were calculated by age categories: cadet, junior, and senior. Furthermore, in cases of unconsciousness resulting from shime-waza, the duration of choking initiation and release, unconsciousness, and awareness were recorded from video analysis and compared by the presence of post-awareness symptoms. A relationship between the duration of shime-waza and the post-awareness symptoms was investigated using receiver operating characteristic analysis. Results: Shime-waza was used to settle 307 (4.1 %) bouts comprising 6.0 %, 4.4 %, and 3.0 % of the cadet, junior, and senior bouts, respectively (p < 0.001). The unconsciousness rates were 18.9 %, 14.6 %, and 4.3 % in the cadet, junior (p = 0.008), and senior bouts (p < 0.001), respectively. Among the 39 unconsciousness cases, 24 (61.5 %) showed convulsions or staggers after awareness. The duration from unconsciousness to choking release in cases with and without symptoms was 5.0 ± 3.5 s and 2.4 ± 2.0 s, respectively (p = 0.009); moreover, this duration was significantly correlated with the duration from unconsciousness to awareness (ρ = 0.480, p = 0.002). The cut-off point for symptom occurrence was a duration from unconsciousness to choking release of ≥4 s (area under the curve = 0.746, p = 0.003, odds ratio = 6.7). Conclusions: Considering the risk of unconsciousness and accompanying symptoms resulting from shime-waza, appropriate education and responses are required.